Conserved versus derived patterns of controlled cell death during the embryonic development of two species of Onychophora (velvet worms). Issue 5 (8th March 2017) - Treffkorn, Sandra; Mayer, Georg
Abstract : Background : Apoptosis is involved in various developmental processes, including cell migration and tissue and organ formation. Some of these processes are conserved across metazoans, while others are specific to particular taxa. Although the patterns of apoptosis have been investigated in arthropods, no corresponding data are available from one of their closest relatives, the Onychophora (velvet worms).Results : We analyzed the patterns of apoptosis in embryos of two onychophoran species: the lecithotrophic/matrotrophic viviparous peripatopsid Euperipatoides rowelli, and the placentotrophic viviparous peripatid Principapillatus hitoyensis . Our data show that apoptosis occurs early in development and might be responsible for the degeneration of extra‐embryonic tissues. Moreover, apoptosis might be involved in the morphogenesis of the ventral and preventral organs in both species and occurs additionally in the placental stalk of P. hitoyensis .Conclusions : Despite the different developmental modes in these onychophoran species, our data suggest that patterns of apoptosis are conserved among onychophorans. While apoptosis in the dorsal extra‐embryonic tissue might contribute to dorsal closure—a process also known from arthropods—the involvement of apoptosis in ventral closure might be unique to onychophorans. Apoptosis in the placental stalk of P. hitoyensis is most likely a derived feature of the placentotrophic onychophorans. Developmental Dynamics 246:403–416, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: The investigation of apoptosis patterns in two onychophoran species revealed similar patterns, suggesting that they are conserved among onychophorans. Apoptosis in the dorsal extra-embryonic tissue during dorsal closure might be conserved in onychophorans and arthropods. Apoptosis in the ventral extra-embryonic tissue might be involved in the morphogenesis of the ventral and preventral organs in onychophorans.